SEJARAH ISLAM MODERN DI IRAN DAN IDE PEMBAHRUAN AYATULLAH KHOEMENI - Saleh Al Hadab; Indo Santalia; Wahyuddin G (Sekolah Tinggi Pariwisata Mataram, 2022)
The Persian Safawi Empire was one of the Muslim political forms at the beginning of the Islamic development. Compared to the two other major empires, namely the Mughals and the Ottomans, the Safawi empire was the most west under pressure. As it is known that the progress of a nation depends on the development of science and technology, it has happened to young people in Iran, causing the country to no longer depend on other countries and to be able to stand on its own. The interest of western countries in pressuring Iran is an interesting thing to discuss. Therefore, the paper aims to examine the history of the development modern Islam in Iran to the idea of ​​reforming Ayatollah Khomeini in Iran. In describing, the author uses historical research methods with a qualitative approach. The results show that the development of Islam in Iran was initiated by Caliph Umar bin Khattab in carrying out the expansion of Islamic territories. However, in the era of the Qajar dynasty (1785/97-1925) and the Pahlavi dynasty (1925-1979) they did not make significant progress towards the development of Islam. The Iranian revolution brought major changes in the political field, by forming a new and independent system of government